Elimination of the income tax advance in Ecuador as a tax obligation (Dissertare, 2020)
A clear way of defining the income tax advance is to pose it as an advance payment of said tax, made in an estimated manner, for a period not yet completed, taking values ​​from previous periods as the basis of the estimate. This payment is usually made in installments. The problem attributed to this collection mechanism is that it generates unfavorable patrimonial and financial effects for companies, since it constitutes a payment for non-existent obligations. In the case of Ecuador, this figure caused controversy, because in some cases it gave rise to payments that exceeded the tax actually caused. The objective of this study is to carry out a literature review with emphasis on the unfavorable and positive aspects of the advance of the income tax in Ecuador, as a way of visualizing the reasons that justified the abolition of its mandatory nature. The work methodology is qualitative, with a documentary design and the application of bibliographic review techniques. Most of the studies on the analyzed mechanism suggest that it negatively affects the liquidity of companies, mainly micro, small and medium-sized companies, due to the amounts paid in excess of the tax caused, without the possibility of compensation or refund. For this reason, there was a strong demand from the business sector regarding the elimination of this tax obligation.